Indoor solid fuel use for cooking and the risk of incidental non-fatal cardiovascular disease among middle-aged and elderly Chinese adults: a prospective cohort study - Xu Chen; Liang Du; Meng Sun; Ling Zhou; Qian Chen; Jia Xu; Haoqiang Ji; Ruiheng Wu; Yunting Chen; Yuanping Pan; Yuxin Duan (BMJ Open)
Objectives The harm of indoor air pollution to health has gradually attracted attention, but the effect of indoor air pollution from burning solid fuels on incidental non-fatal cardiovascular disease (CVD) is not well understood. Under these circumstances, this study examined the association between solid fuel use and incidental non-fatal CVD.Design The prospective cohort study was conducted in 2011, 2013, 2015 and 2018.Setting The nationally representative survey was conducted in 28 provinces of China.Participants This study included 13 544 middle-aged and elderly adults without CVD in the baseline survey, and they were followed for 7 years.Outcome measures First incidence of non-fatal CVD (heart disease or stroke).Methods Based on longitudinal data, Cox proportional hazards models were used to assess the effects of solid fuel use and persistent use on incidental CVD events.Results During the 7-year follow-up period, there were 1533 non-fatal CVD cases. A total of 7310 (54%) participants used solid fuel for cooking at the baseline survey, and 2998 (41%) users continued to use solid fuel. Solid fuel use was associated with incidental non-fatal CVD (HR: 1.18; 95% CI: 1.05 to 1.32) compared with clean fuel, and persistent solid fuel use might lead to a higher risk of incidental non-fatal CVD (HR: 1.38; 95% CI: 1.18 to 1.61) and heart disease (HR: 1.49; 95% CI: 1.24 to 1.81). In the subgroup analysis, the relationship remained significant in the female, elderly, rural and hypertensive groups. However, we found no significant interaction between these risk factors and fuel use (all p<0.05).Conclusions This cohort study provides evidence for the effects of solid fuel use on incidental non-fatal CVD in middle-aged and elderly Chinese adults. Advocating for the use of clean energy and ventilation stoves is important to cardiovascular health.